CLINICAL PRESENTATIONS IN IMMUNE THROMBOCYTOPENIC PURPURA - Farid, Jamila; Gul, Nasreen; Qureshi, Waqar -Ur-Rehman; Idris, Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: Thrombocytopenia is an important cause of mucocutanaeous bleeding in adult and paediatric patients. Immune thrombocytopenia is one of the common causes of thrombocytopenia. Its clinical presentations vary from patient to patient, not studied in our area previously. The present study was planned to see the frequency of clinical presentations of Immune Thrombocytopenic Purpura (ITP) in our patients. Methods: This prospective study was conducted on 125 patients with ITP, diagnosed by exclusion of secondary causes of thrombocytopenia. Bone marrow examination was performed on all the patients. Results: Bruising, epistaxis and gum bleeding were the commonest clinical presentations in adults and children. Bleeding was more severe in acute cases. Increased menstrual bleeding was seen in female patients. Conclusion: Bruising, epistaxis and gum bleeding are the commonest clinical presentations of ITP. Our results are not much different from those of the other studies conducted in Pakistan. Keywords: Thrombocytopenia, Immune thrombocytopenic purpura, mucocutanaeous bleeding